Mahkahmah Konstitusi Sebagai Supremasi Penegakan Etika dan Hukum dalam Masa Pemilu yang Demokratis - rahmad, noor; Dewi, Marsela Artika Sari (JATIJAJAR LAW REVIEW, 2024)
The role of the Constitutional Court is expected to function as a guardian of democracy, a goal that must be achieved as a democracy that upholds sovereignty. There are many rumors about electoral events and opinions that deeply touch on issues of ethics, morals and the philosophy of state democracy. With normative legal research methods which are based on legal principles, synchronization. By using a literature review to research this discussion. There are two things about election violations that must be understood as a society. The first is a process dispute and a result dispute. These two things are different things but influence each other. The ongoing election process influences the results and quality of the nation's democracy. Therefore, from the start, the process must be strictly monitored in terms of law enforcement and ethics so that it reflects the democratic valuesdesired by this people's democratic celebration that is already taking place. Correct enforcement of the constitution is enforcement of the constitution in a fair or just manner. Fair enforcement of the constitution is enforcement of the constitution which provides protection and benefits for every citizen in the context of upholding the supremacy of the constitution as the highest basic law of the state. Handling election disputes by the Constitutional Court (MK) is an important aspect in maintaining integrity and fairness in the democratic process.